Persepsi dan Preferensi Kenyamanan Taman Monumen Perjuangan Kapten TNI Anak Agung Gede Anom Mudita - Wiguna, I Gusti Agung Windar Arya; Sugianthara, Anak Agung Gede; Astawa, I Nyoman Gede (Jurnal Arsitektur Lansekap; Vol.8, No.1, April 2022DO - 10.24843/JAL.2022.v08.i01.p06, 2022)
Convenience perceptions and preferences Taman Monumen Perjuangan Kapten TNI Anak Agung Gede Anom Mudita. Taman Monumen Perjuangan Kapten TNI Anak Agung Gede Anom Mudita has a strategic location right in the center of the city. The interest and awareness of peoples around to utilization Taman Monumen Perjuangan Kapten TNI Anak Agung Gede Anom Mudita as a public space or public area are quite high. However, the comfort value of this public space is still less, there are no facilities like restroom, benches, gazebos and several elements have been broken like statues, lights, paths as far as plants found at some area with faded condition. Those problems becomes idea and also a goal to find out how visitors perceptions and preferences about Taman Monumen Perjuangan Kapten TNI Anak Agung Gede Anom Mudita. This research used a survey as a method with data collection techniques through observation, interviews, questionnaires, and literature study. The results collected about 55.8% of visitors said enough which was seen from nine indicators including circulation, shelter, noise, smells, shape, security, cleanness, beauty, and facilities with diverse preferences. The suggestion that can be given that the government and the management need to improve maintenance, cleanness and adding more facilities with a good arrangement so Taman Perjuangan Kapten TNI Anak Agung Gede Anom Mudita as a public space or public area can function properly.